2018
DOI: 10.1186/s12877-018-0839-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of modified diets to prevent aspiration in oropharyngeal dysphagia: is current practice justified?

Abstract: BackgroundAlthough modifying diets, by thickening liquids and modifying the texture of foods, to reduce the risk of aspiration has become central to the current management of dysphagia, the effectiveness of this intervention has been questioned. This narrative review examines, and discusses possible reasons for, the apparent discrepancy between the widespread use of modified diets in current clinical practice and the limited evidence base regarding the benefits and risks of this approach.DiscussionThere is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 113 publications
2
76
0
2
Order By: Relevance
“…Recipes were developed to meet patients' needs and to be reproducible at patients' homes, which may improve their clinical outcomes. A pilot study in our hospital suggested a strong therapeutic effect of these diets in OD older patients [14], though we also suggested that there was a need for better quality evidence regarding this promising intervention [43]. Recently, Hospital of Mataró and Fundation Furega developed a full set of menus based on the Mediterranean diet, with 2 textures and 2 caloric/proteic adaptations to increase compliance and the pleasure of eating [42].…”
Section: Discussionmentioning
confidence: 99%
“…Recipes were developed to meet patients' needs and to be reproducible at patients' homes, which may improve their clinical outcomes. A pilot study in our hospital suggested a strong therapeutic effect of these diets in OD older patients [14], though we also suggested that there was a need for better quality evidence regarding this promising intervention [43]. Recently, Hospital of Mataró and Fundation Furega developed a full set of menus based on the Mediterranean diet, with 2 textures and 2 caloric/proteic adaptations to increase compliance and the pleasure of eating [42].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for the effectiveness of these behavioural interventions [22], but the modification of food/fluid, particularly with thickening agents, is not necessarily indicated as the preferred management by a number of authors. Although liquid bolus modification has been found to have beneficial effects on bolus flow [40], there is evidence that this impact is not consistent [41], and there are ongoing issues around the consistency of the thickening of liquid [42]. More recently, IDDSI [43] and the European Society for Swallowing Disorders [44] have published recommendations to standardize food consistencies.…”
Section: Clinical Managementmentioning
confidence: 99%
“…For these properties to be fully understood, advanced instruments such as texture analysers and rheometers need to be used. Measurements performed on these instruments can provide some insights that would be useful in the design of TMFs as opposed to instrumental swallowing assessment which are reported to bear little resemblance to eating in real life and swallowing ability at mealtimes (O’Keeffe, ).…”
Section: Rheological Properties Of Tmfs For Dysphagics and The Elderlymentioning
confidence: 99%
“…Patients with OD are reported to be more likely to obtain a better dietary intake with TMFs rather than with normal foods (Sukkar et al , ). Conversely, a lack of evidence to support the significance of thickened fluids and TMFs in relation to the amount of dietary intake for adults with acute dysphagia has been reported (Foley et al , ; O’Keeffe, ). Kaneoka et al reported the lack of evidence for thickened fluids and TMFs in prevention of aspiration pneumonia in patients with chronic dysphagia (Kaneoka et al , ).…”
Section: Rheological Properties Of Tmfs For Dysphagics and The Elderlymentioning
confidence: 99%